2018
DOI: 10.14710/jpk.6.2.108-117
|View full text |Cite
|
Sign up to set email alerts
|

Partisipasi Masyarakat Dalam Pembangunan Prasarana Lingkungan Pada Program PLPBK Di Kelurahan Tambakrejo, Kota Semarang

Abstract: Participation is the participation of a person in a social group to take part of existing community activities, outside of their work. Community participation is needed in a development program because the success of the program is related to community participation in running the program. Tambakrejo village became one of the villages that run the PLPBK program in Semarang City because of a good achievement from BKM. The purpose of this study was to determine community participation in the development of envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…Based on a study conducted by [13], the community participation level at the whole programme steps related to "Community-based Residential Design" -PLPBK actually laid in Informing stage. This confirmed that the information provided by the government to the community was presented one way.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a study conducted by [13], the community participation level at the whole programme steps related to "Community-based Residential Design" -PLPBK actually laid in Informing stage. This confirmed that the information provided by the government to the community was presented one way.…”
Section: Resultsmentioning
confidence: 99%
“…Terdapat beberapa penelitian terdahulu diantaranya Pertama, Penelitian yang dilakukan Makhmudi & Muktiali (2018), ditemukan bahwa Kelurahan Tambakrejo menjadi salah satu kelurahan yang menjalankan program PLPBK (Penataan Lingkungan Permukiman Berbasis Komunitas) di Kota Semarang karena adanya suatu pencapaian yang baik dari BKM. Bentuk partisipasi yang diberikan masyarakat seperti uang, barang, tenaga, dan buah pikiran.…”
Section: Pendahuluanunclassified
“…Seorang ilmuwan bernama Keith Davis mengemukakan pengertian dari partisipasi sebagai keterlibatan mentalitas, moralitas atau perasaan dalam kelompok yang mendorong mereka memberikan kontribusi kepada organisasi dan juga bertanggung jawab atas upaya tersebut. Ini artinya, partisipasi tidak didasarkan pada keterlibatan fisik dalam pekerjaannya, tetapi menyangkut keterlibatan diri orang tersebut sehingga mengarah pada tanggung jawab dan kontribusi besar (Makhmudi & Muktiali, 2018).…”
Section: Partisipasi Masyarakat DI Era Otonomi Daerahunclassified